Forward Collision Prevention System for Two-wheeler Bike Using Berkeley Algorithm-Based PID Control - O. Z. Zhao; V. R. Aparow; Z. M. Jawi; K. A. Abu Kassim (Journal of the Society of Automotive Engineers Malaysia, 2022)
This manuscript summarizes the development of a Forward Collision Prevention (FCP) system for two-wheeler bike dynamics to prevent a frontal collision. A four Degree of Freedom (4-DOF) longitudinal bike model was derived and integrated with the magic tire model. Several handling tests such as the full-throttle acceleration and braking test are performed to validate the developed model. Then the model is then used as a plant to develop the Forward Collision Prevention (FCP) system. The throttle and brake control models were developed to control the throttle level and brake torque of the bike model. A PID controller is implemented with the Berkeley algorithm to overcome the nonlinearity of the entire model. The developed controller can maintain a safe distance of 60m to 70m between the leading vehicle and the two-wheeler bike to prevent a forward collision.